Flow modelling and energy consumption of a hydrotransportation system possessing variable flow boundaries - Pradhan, A.R.; Kumar, S.; Singh, H.; Singh, G.; Saptoro, Agus; Kumar, Perumal (ELSEVIER, 2022)
The design and choice of pipe fittings in such systems plays an important role as far as headloss and flow separation are factors of concern. This study aims to investigate the flow of coal water suspension through a converging section, diverging section and a bend using computational fluid dynamics approach. The modelling and simulation are carried out on geometries consisting of both converging and diverging sections of variable angles along with a bend of R/d ratio of 2. The computational fluid dynamics simulation results are in good agreement with the experimental data, with an average percentage error of 1.96%. 1° angle of divergence and 7° angle of convergence are optimum designs for the lowest local headloss. However, the headloss across the entire test section is found to be minimum for the case where the angle of convergence/divergence is fixed at 1° each. The specific energy consumption gives a practical idea about the minimum energy required for the transportation of solids through some distance, which is an all-time minimum for the suspension containing 60% solids by mass. The study presents a detailed investigation into the local as well as global flow characteristics of the coal water suspension through a test section.